1992
DOI: 10.1017/s0025315400048785
|View full text |Cite
|
Sign up to set email alerts
|

Regional morphological variations in the compound eyes of certain mesopelagic shrimps in relation to their habitat

Abstract: The anatomy of the eyes of several species of mesopelagic decapods (family Oplophoridae), obtained from the eastern north Atlantic, is described and related to the unique light environment of the deep seas. The oplophorid eyes are of the reflecting superposition type, but they show a number of regional morphological variations. The main rhabdom, formed by retinula cells Rl to R7, comes in a variety of shapes, from fusiform rhabdoms in the dorsal region of the eyes of Oplophorus spinosus to multi-lobed interdig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
39
0

Year Published

1995
1995
2014
2014

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(40 citation statements)
references
References 33 publications
1
39
0
Order By: Relevance
“…Both apposition Schiff et al, 1986;Cronin et al, 1994) and superposition eyes (Elofsson and Hallberg, 1977;Hiller-Adams and Case, 1988;Gaten et al, 1992;Richter, 1999) probably as an evolutionary consequence of environmental pressures, may display further structural and functional modifications. Forms, for instance, that flourish in extreme environments (mesopelagic and deep-sea crustaceans, and species adapted to a life underground or in caves) frequently exhibit morphologies that differ from the basic design (Meyer-Rochow and Nilsson, 1999).…”
Section: Crustacean Compound Eye: Basic Structurementioning
confidence: 99%
See 1 more Smart Citation
“…Both apposition Schiff et al, 1986;Cronin et al, 1994) and superposition eyes (Elofsson and Hallberg, 1977;Hiller-Adams and Case, 1988;Gaten et al, 1992;Richter, 1999) probably as an evolutionary consequence of environmental pressures, may display further structural and functional modifications. Forms, for instance, that flourish in extreme environments (mesopelagic and deep-sea crustaceans, and species adapted to a life underground or in caves) frequently exhibit morphologies that differ from the basic design (Meyer-Rochow and Nilsson, 1999).…”
Section: Crustacean Compound Eye: Basic Structurementioning
confidence: 99%
“…1981a; Gaten et al, 1992). What is more, new findings have shown that regional differences are present in the eyes of many crustaceans and not just those adapted to extreme environments (Odselius and Nilsson, 1983;Tokarski and Hafner, 1984;Cronin et al, 1992;Zeil and Zanker, 1997), highlighting the need for additional research into how the various regions of a compound eye behave (and perhaps influence each other) and how, more generally, post-embryonic eye differentiation occurs (cf., Meyer-Rochow et Ziedins and MeyerRochow, 1990;Tokarski, 1998, 2001).…”
Section: Crustacean Compound Eye: Basic Structurementioning
confidence: 99%
“…They have reflecting superposition eyes with large rhabdoms, characteristics that lead to high sensitivity. Several anatomical studies have described interspecific and intraspecific variations in eye morphology that are related to the depths at which the species are normally found (Welsh & Chace, 1937, 1938Gaten et al, 1992Gaten et al, , 2003. In particular, considerable variations in the relative sizes of the distal and proximal rhabdoms have been described (Gaten et al, 2003), although the reason for these differences has not been fully explained.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, it is of paramount importance in designing experiments in aquaria to consider the light environment carefully. Light is a key determinant of behaviour of mesopelagic organisms and they tend to be specifically adapted to cope with a particular light intensity, in addition to defined spectral, spatial and temporal distributions of light (Gaten et al, 1990(Gaten et al, , 1992Johnson et al, 2000aJohnson et al, , 2000bJohnson et al, , 2002. Failure to consider these important factors is likely to lead to anomalous behaviour, physiological damage and erroneous conclusions.…”
Section: Resultsmentioning
confidence: 99%